Tailing dams formation algorithm - Lolaev, Alan; Oganesyan, Aleksan; Badoev, Alexander; Oganesyan, Emil (Arabian journal of geosciences, 2020)
The object of research of the present work is the tailing dump, located on the territory of north of Siberia . Based on the operating conditions of alluvial storage in permafrost, it should be noted that the increase in the annual capacity of the layer may not provide its complete consolidation during short spring-summer period before freezing. Thus, it will reduce the stability of the structure. In order to optimize the inwash technology of tailing dam, it is necessary to determine the time of tail’s consolidation. On the basis of laboratory tests, the approach to coefficient definition of filtrational and secondary consolidation of tails during alluvium depending on a physical condition, density, water saturation degree, and the mathematical model to calculate the time of their consolidation has been developed. The results obtained from researches can be successfully used as a basis for constructing consolidation models of required layer tails.